L’argotisme dans les milieux estudiantins de la ville de Kisangani. - Lukombe, Jacques MUKONKOLE (IJRDO- Journal of Educational Research, 2021)
This article concerns the slang language used by students in the city of Kisangani. It is not only a question of contextualizing the use of the listed lexies but also of determining the semantics related to them. This language is used by students in order to stand out from other local socio-professional groups.  Thus, they are distinguished by a particular language not only in their study environments, but also wherever they can meet: in the city, in the city, in the market, at the stadium, in short in any public or private environment. The themes exploited in the lexies listed relate to academic life, sexuality or food. As for the processes used, they relate in particular to borrowing, neologism, metaphor and derivation.